1997
DOI: 10.1021/la970266s
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Pore Volume in Adsorption Experiments and Theoretical Models

Abstract: We propose a new definition of excess adsorption for use in molecular models of adsorption. This definition implies the calibration of theoretical models in a manner mimicking the experimental calibration procedure. The method of theoretical calibration is developed on the example of helium calibration. The notions of the He calibrated pore volume and the He calibrated pore size are introduced, and the He calibrated theoretical excess isotherms are defined. The proposed method diminishes the discrepancies betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 34 publications
1
114
0
1
Order By: Relevance
“…This effect can be reduced by measuring the density at higher temperatures, but we found that on IGA an increase in temperature introduced an instability in the sample mass caused by convection. At 308K, the ratio between "He pore widths" and the geometrical pore widths in the range of 3Å -10Å is predicted to be about 1.25 -1.5 [26]. Hence, the "He density" of the nano-pore carbon can be ca.…”
Section: Sans Data Measured Using Variable Contrastmentioning
confidence: 97%
See 1 more Smart Citation
“…This effect can be reduced by measuring the density at higher temperatures, but we found that on IGA an increase in temperature introduced an instability in the sample mass caused by convection. At 308K, the ratio between "He pore widths" and the geometrical pore widths in the range of 3Å -10Å is predicted to be about 1.25 -1.5 [26]. Hence, the "He density" of the nano-pore carbon can be ca.…”
Section: Sans Data Measured Using Variable Contrastmentioning
confidence: 97%
“…It is known that helium density measurements in these materials performed at room temperature can be erroneous [25]. Indeed, GCMC calculations suggest [26] that the average density of helium confined in sub-nanometer pores may exceed the bulk density by orders of magnitude due to gas interaction with the surface. This makes the pores look bigger than they actually are and hence the matrix density determined by He picnometry comes out higher than it should be.…”
Section: Sans Data Measured Using Variable Contrastmentioning
confidence: 99%
“…Consequently, their properties are unknown functions of the bulk gas phase pressure and system temperature. Therefore, the experimentally observed mass change in the sample is represented as the difference between the total adsorbed amount and the bulk density of the adsorbate, which is expressed by a simple equation: 24,25 N total = N excess + r bulk V pore (1) where N total is the total adsorbed amount, N excess is the excess amount, r bulk is the bulk density of H 2 , and V pore is the pore volume of an adsorbent. Thus, most experimental measurements are reported as an excess adsorption amount.…”
Section: 12mentioning
confidence: 99%
“…The a and b parameters varies less than 3% in comparison to pristine CAU-10, while the c parameter vary less than 2%. Table 2 shows the calculated pore volume available for Helium adsorption [21] using CAADS code and the accessible solvent surface area computed using the module "Atom Volumes & Surfaces" implemented in Material Studio software [20]. The CAU-10Thiophene presents the highest surface area of 860.71 Ų and the highest pore volume of 0.47 cm 3 /g, while the CAU-10Pyran presents the smallest values of surface area, equals to 672.71 Ų, and pore volume equals to 0.39 cm 3 /g.…”
Section: Discussionmentioning
confidence: 99%